Malnutrition and associated risk factors in pre-school children (2-5 Years) in district Swabi (NWFP)-Pakistan - Khattak, Muhammad Muzaffar Ali Khan; Ali, S. (Ansi Network for Scientiific Information, 2010)
To assess the nutritional status and the associated risk factors in preschool age children in the District Swabi of the North West Frontier Province (NWFP)-Pakistan. The studies included 140 children (both boys and girls) and were assessed for nutritional status using correlation analysis for association of malnutrition with parent’s income, family size and number of the child within the family, sex of the child and Z-score for stature/age, weight/age/stature and weight/stature. The results showed no significant differences between the sex, age for weight and height compared. The weight and height were lower than the third percentile in all cases and indicate that the children were stunted and under-weight. The mean z-score in every case (i.e., -score for age-height and age-weight, sex-height and sex-weight and height-weight) was significantly different. Furthermore, there was strong association of malnutrition with family size, income of the parents and child number in the family in rural areas. This study indicates that the children in this particular area on average are at the risk of malnutrition due to large family size and lower income.